A Heritage Economy: Business Model Innovation for Economic Wealth, Social Well-Being, and Environmental Health - Frédérick Brousseau-Gauthier; Yvon Brousseau (Technology Innovation Management Review, 2013)
Faced with the inherent unsustainability of infinite growth in a world of finite resources, the neoclassical economy is running towards a cliff. In order to avoid a hard landing, enterprises need to broaden their definitions of value and wealth to include parameters that are not currently in the economic lexicon, but are still of paramount importance in our lives. Taken from that angle, heritage can be seen as a perfect replacement for capital, because its multidimensional and complex nature opens up numerous possibilities for the creation of shared economic, social, and environmental value; the designing of value chains; and the direction of technological innovation. This article explores the various ramifications of a paradigm shift from managing capital to managing heritage, and it underlines the need to create a series of pioneering business models for enterprises to adapt and profit from a new, heritage economy.